Genesis, development, and current challenges of the Regional Institute for Toxic Substance Studies (IRET) - Castillo, Luisa Eugenia (2026)
The Central American Institute of Studies on Toxic Substances, IRET, was born in 1998 within the School of Environmental Sciences at Universidad Nacional, built upon work on pesticides since the 1980´s decade. It has contributed to the knowledge of the use and impact on the environment and health of pesticides and other emerging contaminants like antibiotics and plastics with emphasis on coastal zones, rivers, creeks and agricultural ecosystems. In the field of health, it has studied occupational and childhood cancer, occupational and environmental exposure to pesticides, and the exposure to heat. It promotes the use of agroecological practices and clean technologies in agriculture and generates qualitative and quantitative information of imported pesticides and their uses in Costa Rican agricultural activities. The focus of the Institute includes not only the evaluation of risks but also a contribution to the search for solutions and risk prevention. It has a laboratory specialized in analytical chemical techniques (LAREP) and another in ecotoxicological studies (ECOTOX) as well as three academic programs: Master’s in Occupational Health, Master’s in Ecotoxicology and Masters in Bioethics. Some of the keys to the success of IRET have been its scientific and multidisciplinary work in collaboration with governmental and non-governmental organizations within the country, with other academic units at UNA and with other state universities and regional and international collaboration. Given its experience and knowledge IRET should and can be a strong ally in the search for solutions to the use and emissions to the environment of toxic substances and to the prevention of their impact on health and the environment.